Training and development challenges in the Office of the Premier, Limpopo Province - Nkoana, Noko Josephine (My University, 2023)
The accomplishment and success of organisational goals and objectives depend on the performance of the employees. Hence, it is essential for an organisation to invest in training and development to improve employee performance. Training and development primarily deal with improving employees’ skills and knowledge needed to perform their tasks at the workplace and again to increase and grow them for the future levels of management. The organisation must have skilled employees who have the capacity to reach the objectives and future challenges of the organisation. This study aims to identify training and development challenges (T & D) in the Office of the Premier, Limpopo Province and to suggest possible strategies to address those challenges. The qualitative research design method was used in the study. Data was collected using a semi-structured interview, which consisted of openended questions. Based on the findings of this study, it was discovered that there are challenges that impede service delivery in the Office of the Premier T&D. The implementation of training and development in the Office of the Premier significantly led to an increase in the performance of employees. The study focus was limited only to the Limpopo Office of the Premier, but the findings and the recommendations may benefit other provincial departments and be of interest to scholars of Public Administration and Management as well. The challenges identified in the study include; an insufficient budget, a lack of staff, limited support from the management; no post-appraisal training methods; and nonutilisation of HRD benefits by the employees in the Office of the Premier. Recommendations and possible solutions were made regarding the identified training and development challenges, which may be of value for possible future research.
Thesis (MPAM.) -- University of Limpopo, 2023
Keywords: Employees; Office of the Premier; Performance; Training and development; Employee orientation; Employee empowerment; Employees -- Training of -- South Africa -- Limpopo